2018
DOI: 10.21873/anticanres.12859
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen and Neutrophil-to-lymphocyte Ratio Predicts Survival in Patients with Advanced Hypopharyngeal Squamous Cell Carcinoma

Abstract: F-NLR score was useful to stratify patients to extract poor prognostic characteristics in patients with advanced HPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The findings from the present study showed some relationships between peripheral blood hematological and serological parameters, patient demographics, clinicopathologic characteristics, and patient prognosis in LSCC. There have been previous reports that high preoperative plasma levels of fibrinogen correlated with poor patient survival in esophageal squamous cell carcinoma [40,41] and advanced hypopharyngeal squamous cell carcinoma [42]. Pretreatment measurement of the NLR and the platelet-to-lymphocyte ratio (PLR) have been shown to be a useful complement to TNM staging in the prognostic assessment of patients with nasopharyngeal carcinoma (NPC) [43].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from the present study showed some relationships between peripheral blood hematological and serological parameters, patient demographics, clinicopathologic characteristics, and patient prognosis in LSCC. There have been previous reports that high preoperative plasma levels of fibrinogen correlated with poor patient survival in esophageal squamous cell carcinoma [40,41] and advanced hypopharyngeal squamous cell carcinoma [42]. Pretreatment measurement of the NLR and the platelet-to-lymphocyte ratio (PLR) have been shown to be a useful complement to TNM staging in the prognostic assessment of patients with nasopharyngeal carcinoma (NPC) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies were conducted in China, and six in Japan. Five different types of DSCs were assessed in this study, including esophageal carcinoma (EC) ( 4 , 8 , 13 , 17 , 18 ), gastric cancer (GC) ( 5 , 6 , 11 , 14 , 16 , 20 ), colorectal cancer (CRC) ( 10 , 12 , 19 ), hypopharyngeal carcinoma (HPC) ( 9 ), hepatocellular carcinoma (HCC) ( 7 , 15 ). The characteristics of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a new scoring system, termed fibrinogen and neutrophil-lymphocyte ratio (F-NLR), that combines pretreatment fibrinogen levels with neutrophil-lymphocyte ratio (NLR) has gradually attracted considerable research attention. The F-NLR score has been reported as a promising prognostic marker in patients with DSCs (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). However, the results remain controversial.…”
Section: Original Articlementioning
confidence: 99%
“…Advances in treatment techniques may improve the survival rate; however, risk stratification is also important in developing an individualized treatment management schedule. To date, researchers have made efforts to identify prognostic factors, including clinical features (21), cellular adverse factors (22,23) and molecular markers (24,25). This information can be used to identify patients with high-risk HNSCC who may benefit from more aggressive therapy and frequent follow-up following primary treatment.…”
Section: Discussionmentioning
confidence: 99%